RESVECH 2.0: cross-cultural adaptation for Brazil, reliability and validity for the evaluation of venous ulcers - Marina Rosa Menegon; Suelen Gomes Malaquias; Joana Aragão da Silva; Beatriz Guitton Renaud Baptista de Oliveira; Juan Carlos Restrepo Medrano; José Verdú-Soriano; Maria Márcia Bachion (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to cross-culturally adapt the scale Resultados en la valoración y evolución de la cicatrización de las heridas - RESVECH 2.0 for Brazilian Portuguese; to estimate the internal consistency and construct and criterion validity of the scale in the evaluation of venous ulcers. Methods: methodological study, based on international guidelines for studies of this type. Wounds were evaluated using the RESVECH 2.0 and Pressure Ulcer Scale of Healing 3.0 (PUSH). Descriptive analysis, confirmatory factor analysis, Cronbach's alpha and Spearman's correlation (p<0.05) were used. Results: 12 nurses and 77 people with 153 venous ulcers participated in the study. The translation was successful, the proposed factor model was validated, and Cronbach 's alpha = 0.832 (95%CI, 0.780-0.880) and correlation coefficient (RESVECH 2.0 and PUSH 3.0) = 0.74 were obtained. Conclusions: the adaptation of RESVECH 2.0 to Brazilian Portuguese is robust. Reliability and validity show compatibility for use in the country in the evaluation of venous ulcers.